Preserving Local Traditions in the Digital Age: Adapting the 'Mapak Tanggal' Ritual as an Intergenerational Solution - Gunagraha, Shindid; Kholilurrahman, Kholilurrahman (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2024)
This research focuses on the preservation of the